Development of regional downscaling capability in STEAMER ocean prediction system based on multi-nested ROMS model. Issue 8 (3rd August 2019) - Kamidaira, Yuki; Kawamura, Hideyuki; Kobayashi, Takuya; Uchiyama, Yusuke
ABSTRACT: Oceanic regional downscaling capability was implemented into Short-Term Emergency Assessment system of Marine Environmental Radioactivity (STEAMER) developed by Japan Atomic Energy Agency to enable us to predict more realistically the oceanic dispersion of radionuclides at higher spatiotemporal resolutions for broader applications. The system consisted of a double-nested oceanic downscaling circulation model with tidal forcing and an oceanic radionuclide dispersion model. This system was used to comparatively examine downscaling and tidal effects on the dispersion of radionuclides hypothetically released from the Fukushima Daiichi Nuclear Power Plant in the colder season. The simulated dissolved 137 Cs distribution was different from that obtained using coarser-resolution models because downscaling enhanced both horizontal and vertical mixing. The suppression of horizontal mixing and the promotion of vertical mixing by tidal forcing synergistically reduced offshore 137 Cs transport. In addition, the submesoscale effects strengthened the three-dimensional 137 Cs fluctuations by <10 times, while the tidal effects promoted slightly increased the intensity of three-dimensional 137 Cs fluctuations by approximately 3%. This indicated that the submesoscale effects substantially surpassed tidal forcing in oceanic mixing in the coastal margin off Fukushima in the colder season.